2011
DOI: 10.1111/j.1525-1594.2011.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Wound Dressing With Artificial Capillaries for Temporary Wound Irrigation and Skin Cell Supply

Abstract: Medical treatment of burns and chronic wounds remains a challenge. We discussed a therapy concept that combines skin cell spray transplantation with a novel wound dressing based on artificial hollow fiber membrane capillaries. In skin cell-based therapy development, autologous skin progenitor cells are isolated from a healthy skin area and sprayed onto the wound. A medical device was introduced that uses perfused capillaries, known from clinical plasma separation, as a temporarily applied extracorporeal wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Polymer Characterization. 1 HNMR spectra of the PUUs were recorded with a 300 MHz Bruker spectrometer using DMSO-d 6 as solvent. Intrinsic viscosities of PUUs at 25 °C were measured (n = 3) with HFIP as a solvent using an Ubbelohde viscometer.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Polymer Characterization. 1 HNMR spectra of the PUUs were recorded with a 300 MHz Bruker spectrometer using DMSO-d 6 as solvent. Intrinsic viscosities of PUUs at 25 °C were measured (n = 3) with HFIP as a solvent using an Ubbelohde viscometer.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These results are similar to previous findings that galanin expression throughout the hypothalamus, as a whole, is not sexually dimorphic in sheep (8,28). This is also in contrast to what is observed in rodents, as galanin expression is found to be highly sexually dimorphic in both mice (51) and rats (16). One report observed a slightly stronger intensity of galanin staining in male compared to female sheep and suggested that this neurons and the degree to which these populations participate in the LH surge remains unknown.…”
Section: Discussioncontrasting
confidence: 68%
“…Jorn Plettig et al. of the Universitätsmedizin Berlin, Berlin, Germany described their therapy concept that combines skin cell spray transplantation with a novel wound dressing based on artificial hollow fiber membrane capillaries. Autologous skin progenitor cells are isolated from a healthy skin area and sprayed onto the wound.…”
Section: Tissue Engineeringmentioning
confidence: 99%